Proteção jurisdicional efetiva na União Europeia: evolução e perspetivas (ou expetativas) futuras - Proença, Carlos (Debater a Europa, 2016)
In its evolution, the European Union’s judicial protection system has attributed legal force to the Charter of Fundamental Rights and is considering the prospective accession of the Union to the European Convention of Human Rights. These and other changes - such as the possibility of convicting Member States in financial penalties in the same proceeding for failure to fulfil an obligation, as well as the possibility for individuals or institutions to bring action for annulment of regulatory acts - were introduced by the Treaty of Lisbon. However, as it consecrated the right to effective judicial protection, this Treaty missed yet another opportunity of granting to the Ombudsman of the European Union the legitimacy to challenge legislative acts; at the same time, we would like to be given a chance to achieve a reversal in the Foto-frost jurisprudence, which denied to domestic jurisdictional bodies the prerogative to invalidate European provisions. https://doi.org/10.14195/1647-6336_15_4